ELEKTRONİK YAYINCILIK ÜZERİNE - Ahmet Çelik (Türk Kütüphaneciliği)
Printing industry is one of the areas affected by lb developments in computers and telecommunications. Some experts argue that electronic publication, which is a product of such developments mentioned will replace the printing indusrty based on paper. In this paper, electronic publication and its possible effects on publishers and libraries are briefly discussed.